The self-directed teacher - Nunan, David (Cambridge University Press, 1996)
This text provides the practical knowledge and necessary skills for the effective management of teaching and learning in today's classrooms. It focuses on the independent decisions teachers must make in lesson planning, group work, error correction, resource management, and evaluation. A task-based approach is used, and the material presented is well supported by theory and research. Advances in second language teaching methodology, including new emphases on learner centeredness and individualized instruction, have significantly changed the roles teachers play in the classroom and made ever-greater demands on their classroom management skills. This book helps language teachers meet these new demands by providing them with the practical knowledge and skills necessary for the effective management of teaching and learning in today's classrooms